1959
DOI: 10.1139/m59-076
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Decomposition of Rutin

Abstract: A number of molds, streptomycetes, and bacteria, obtained from culture collections and by enrichment techniques, were tested for their ability to degrade rutin. The molds, particularly Aspergillus fiavus and A. niger, appeared to be more active than either the streptomycetes or bacteria. The aspergilli when grown on either rutin or quercetin produced extracellular enzymes that degraded both rutin and quercetin but not quercitrin. Rutinose, protocatechuic acid, phloroglucinol carboxylic acid, and a phloroglucmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

1963
1963
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 9 publications
2
46
0
1
Order By: Relevance
“…12: Fungi (Siqueira et al, 1991b). 13: Aspergillus flavus and Aspergillus niger (Simpson et al, 1960;1962;Westlake et al, 1959). 14: P. putida (Schultz et al, 1974).…”
Section: Biological Activity Of Flavonols and Their Degradation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…12: Fungi (Siqueira et al, 1991b). 13: Aspergillus flavus and Aspergillus niger (Simpson et al, 1960;1962;Westlake et al, 1959). 14: P. putida (Schultz et al, 1974).…”
Section: Biological Activity Of Flavonols and Their Degradation Productsmentioning
confidence: 99%
“…14: P. putida (Schultz et al, 1974). 15: A. flavus and A. niger (Simpson et al, 1960;Westlake et al, 1959). 16: Bacteria from gut (Konishi, 2005) and liver/kidney (Olthof et al, 2003).…”
Section: Biological Activity Of Flavonols and Their Degradation Productsmentioning
confidence: 99%
“…Seiler (1978) demonstrated that soil liberates small amounts of CO and that the rate of CO production increases when the soil temperature exceeds 40 ° C. CO liberation by different soils in different climatic areas varies, but in relatively humid soils of temperate regions, CO consumption is 5 to 10 times higher than the CO liberation (Conrad & Seiler 1985a,b). CO is also produced by a number of living beings and occurs as a product during the degradation of the c~-methine bridge in porphyrins by mammals, green and red algae, and cyanobacteria (Troxler 1972;Troxler & Dokos 1973;Yoshida et al 1982) as well as during the degradation of flavonoides, quercitrin, and rutin by fungi (Westlake et al 1959;Simpson et al 1960Simpson et al , 1963. Marine animals of the order Siphonophora produce substantial amounts of CO in their pneumatophores (Hahn & Copeland 1966;Wittenberg 1960;Wittenberg et al 1962;Pickwell et al 1964;Pickwell 1970) and the brown alga Nereocystis luetkeana contains, in addition to other gases (e.g.…”
Section: A Sources Of Comentioning
confidence: 99%
“…[ (9) or [Cu(fla)(iPr-TAC)]ClO 4 (10) (fla ϭ flavonolate) were isolated as crystalline solids in yields of 95 and 90%, respectively (Scheme 2). The reaction products were identified on the basis of spectroscopic ] are due to chelation and formation of stable five-membered rings.…”
Section: Introductionmentioning
confidence: 99%